THE ROLE OF SOCIAL MEDIA IN THE IMAGE OF THE LHOKSEUMAWE CLASS II TPI IMMIGRATION OFFICE - Nailul Authia; Siti Safwani Hizqia Nabila; Azzahra Naurah Mawaddah; M. Riva Faruqi; Halimatus Sa'diyah; Elvina Elvina; Nursyidah Nursyidah (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
This study aims to determine the role of social media in building the image of the Class II TPI Lhokseumawe Immigration Office in the digital era. In the context of public services, the agency's image greatly determines public trust in government performance. Therefore, the use of social media is one strategy in bringing services closer to the public. The research method used is a descriptive method with a qualitative approach. Data were obtained through observation, interviews, and documentation of posts and interactions provided by the public. The results show that the use of social media by the Class II TPI Lhokseumawe Immigration Office has played a fairly effective role in building a positive image through fast, transparent information delivery and direct interaction with the public. However, there are obstacles in the image building process, namely the interaction provided by the public is still relatively low. This is indicated by the minimal comments, likes, and shares given by the public. However, this does not hinder the dissemination of information disseminated by the Class II TPI Lhokseumawe Immigration Office to the public.